Analysis of Pattern Rice Businesses Legoo Crops 2:1 and Tegelin District Moncongloe, Maros Regency - Muhamad Ilham; Yunus Musa; A. Nixia Tenriawaru (International Journal of Science, Technology & Management, 2021)
This study aims to analyze the productivity and income of farmers on the pattern row planting legowo and tiles as well as formulate alternative strategies that are appropriate for the development of paddy rice rain-fed in an effort to increase productivity and income of farmers in the District Moncongloe Maros Regency of South Sulawesi. The research method used is purposive sampling based on the type of rice varieties used, namely Inpari 33 with the pattern of row planting legowo and tiles as well as rainfed land. The sample taken is a member of the farmer group Biring Jene 1 and farmer group Biring Jene 2. Two of these groups are selected because members of this group there that uses the pattern legowo row planting and using varieties Inpari 33. The results of the research that the amount of revenue jajar legowo higher compared to tiles with at 9.358,3 kg/Ha or Rp. 42.112.350 to forecast legowo row planting and 4.185,4 kg/Ha or Rp. 18.834.449 for the reception of grain production in the cropping pattern tiles, with a difference of the receipt of such production of 5.172,9 kg/Ha or Rp. 23.277.901 and the value of the R/C ratio of 1,53 jajar legowo and of 1.49 for the tiles. The formulation of the strategy of SWOT analysis is a Strategy S-O, among others, the Development and improve the human resource capabilities of farmers in agricultural technology innovation, strategy W-O, among others, improve the ability mastery of appropriate technology for farmers, the strategy S-T, among others, the optimization of the agricultural land and the strategy of W-T, among others, use varieties that are resistant to PEST and disease and able to survive extreme conditions.